1987
DOI: 10.1080/08940630.1987.10466303
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization and Optimization of the AgNO3-Filter/FMA Fluorimetric Method for Atmospheric H2S Measurements

Abstract: This sensitive, albeit precarious, method for measuring ppb-ppt (V/V) concentrations of H 2 S was examined for various sources of potential error within the procedure. Filter preparation, filter storage, filter extraction, fluorimetric reagent stabilities, matrix differences between standards and samples, and possible interferences from other sulfur-containing compounds were separately studied for their effects on the analytical performance of the method. The overall method showed no Interference from SO 2 , C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Axelrod et al [14] found no significant interference from sulfate but a small effect from sulfite. Farwell et al [15] reported that there was no statistically significant interference observed from SO 2 , CS 2 , COS, CH 3 SH, or CH 3 SCH. Table 5 summarizes our results.…”
Section: Interferencementioning
confidence: 98%
See 1 more Smart Citation
“…Axelrod et al [14] found no significant interference from sulfate but a small effect from sulfite. Farwell et al [15] reported that there was no statistically significant interference observed from SO 2 , CS 2 , COS, CH 3 SH, or CH 3 SCH. Table 5 summarizes our results.…”
Section: Interferencementioning
confidence: 98%
“…Quantification is achieved by the selective quenching effects of sulfide (S -2 ) on the fluorescence of fluorescein mercury acetate (FMA) measured by a filter fluorometer (Sequola-Turner Model 450, supplied by Waterman LabSales, Hillsboro, OR). Details of the analytical methodology have appeared elsewhere [14,15].…”
Section: A Permeation Oven To Generate Known H 2 S Concentrations (Momentioning
confidence: 99%
“…At the end of each sampling interval, air samples were shipped to the laboratory of Maxxam Analytics in containers sealed with Teflon tape [14]. The sulfate ions were then extracted from the sampling media with a hydrogen peroxide solution in ultra pure distilled/deionized water.…”
Section: Sulfur Dioxide Measurementsmentioning
confidence: 99%
“…These were prepared by dilution of a 10 -6 M solution of sodium sulfide (Na 2 S) using the NaCN extracting solution. The use of S 2-aqueous standards instead of gaseous ones is adequate, although there is a risk of underestimating the precision of the method (Farwell et al, 1987).…”
Section: Sampler Analysismentioning
confidence: 99%